Brahma flanked by his two consorts on the Devakoshthas (niches) - Temples of India Project Team (Jio Institute, 2024)
The south-facing transept of the mandapa (pillared hall) in the Mahanaleshwar Temple is identical to the north elevation. There are three devakoshthas (niches) on the dwarf wall of the mandapa. The central devakoshtha has a figure of Brahma holding a pustaka (book) and kamandalu (water carrier or pot), and the two flanking devakoshthas have consorts of Brahma, one of them is depicted with three faces. The wall between these devakoshthas is designed with pilaster motifs and interspersed with surasundaris (celestial damsels).